PENGARUH SOCIAL MEDIA MARKETING ACTIVITIES TERHADAP PURCHASE INTENTION MELALUI BRAND EQUITY PADA PLATFORM NETFLIX DI KOTA PEKANBARU - Zulfadli Zulfadli; Deny Danar Rahayu; Sharnuke Asrilsyak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study aims to determine the effect of Social Media Marketing Activities on Purchase Intentionthrough Brand Equity on Netflix Platform in Pekanbaru City. The sampling technique used nonprobability sampling with purposive sampling type, and data were obtained by distributingquestionnaires to 120 respondents. The approach used in this study is a quantitative approach withthe SEM-PLS model and processed using SmartPLS 4.0 software. The results of the study indicate thatthere is a positive and significant effect of Social Media Marketing Activities on Brand Equity onNetflix Platform in Pekanbaru City. There is a positive and significant effect of Social MediaMarketing Activities on Purchase Intention on Netflix Platform in Pekanbaru City. There is a positiveand significant effect of Brand Equity on Purchase Intention on Netflix Platform in Pekanbaru City.There is a positive and significant effect of Social Media Marketing Activities on Purchase Intentionthrough Brand Equity on Netflix Platform in Pekanbaru City. This study is expected to be a referencefor further research, and can conduct research development by adding other variables or expandingthe scope of the research area.Keywords: Social Media Marketing Activities, Purchase Intention, Brand Equity